On Generalized Lipschitzian Semitopological Semigroup of Self-Mappings With Applications - Imdad, M.; Barakat, Mohamed A.; Soliman, Ahmed H. (Sarajevo Journal of Mathematics, 2024)
In this paper, we use a generalized Lipschitzian type condition for a semigroup of self-mappings as employed in Imdad and Soliman (Fixed Point Theory Appl. Vol. (2010), Article ID 692401, 1-14) to prove a fixed point theorem for a generalized Lipschitzian left reversible semitopological semigroup of self-mappings defined on a p-uniformly convex Banach space, besides indicating some possible applications to our main result. Our results generalize and extend some results due to J. S. Jung and B. S. Thakur (Inter. Jour. Math. Math. Sci., 28 (1)(2001), 41-50). 2000 Mathematics Subject Classification. 47H10, 54H25